Investigating the Morphology of the Iranian Bazaar with Urban Spatial Design Approaches, Case Studies: Kerman and Shiraz Bazaars - Azadeh Lak; Pantea Hakimian (صفه)
The bazaar, like the heart of Iranian towns, not only delivers social, cultural, and economic functions but also functions as the most significant urban space forming the town structure. Incongruous development in recent decades has led to the deterioration of central town fabrics and has impaired the physical, economic, and social life in the bazaars, marking a challenge for urban regeneration initiatives. This research aims to carry out a deep study of the morphology of the Iranian bazaar in order to preserve the most important urban element in the spatial-cognitive structure of the historic cities of Shiraz and Kerman. The research, using a qualitative and descriptive-analytical method, initially attempts to analyze the bazaars in Shiraz and Kerman according to Trancik’s theories of urban spatial design (1986) using library material including maps. In the second step, in-depth interviews were conducted with 10 residents of Shiraz and 11 residents of Kerman using snowball sampling investigating the meaning of the bazaar using content analysis. The results show that the Iranian bazaar is an “urban solid” space with an axial/angular organization typology, functioning as a coarse urban block or an armature of geometric open spaces. According to linkage theory, the bazaar is a “group form” and a “mega form” articulating the old town spaces. According to place theory, the bazaar is the most important historical element and a landmark for the inhabitants of the town, posing a unique physical form and architectural style, housing trade activities, and an urban tourism center. The results of this research can lead to design solutions for urban designers and planners in urban regeneration projects.